Optimal Soil Management and Environmental Policy - Gilles Lafforgue; Walid Oueslati (Fondazione Eni Enrico Mattei (FEEM), 2005)
This paper studies the effects of environmental policy on the farmers soil optimal management. We consider a dynamic economic model of soil erosion where the intensity use of inputs allows the farmer to control soil losses. Therefore, inputs use induces a pollution which is accentuated by the soil fragility. We show, at the steady state, that the environmental tax induces a more conservative farmer behavior for soil, but in some cases it can exacerbate pollution. These effects can be moderated when farmers introduce abatement activity.
Keywords: Q12; Q24; Q28; Q52; H23; 330; Soil erosion; Pollution; Environmental policy; Optimal soil conservation; Abatement activities